Chicago mercantile exchange bitcoin futures: Volatility, liquidity and margin - Carl F. Luft; Jin Man Lee; Jin W. Choi (SPOUDAI - Journal of Economics and Business, 2019)
This paper explores empirically the behavior of the Chicago Mercantile Exchange (CME) bitcoin futures contract. The analysis focuses on the time period between the launch of the CME bitcoin futures contract on December 18, 2017, and September 17, 2018. The behavior of the bitcoin spot market and CME futures market is compared and analyzed along several dimensions: price, volatility and liquidity. By comparing the Garman-Klass volatilities of bitcoin spot and futures prices with those of different assets, we find that both the bitcoin spot and futures markets exhibit relatively high volatility compared to other assets. When the ratio of trading volume over open interest is used to measure liquidity, the bitcoin futures market shows a mid-level liquidity. We also find while the exchange margin is set to meet the normal price volatility that can cover the daily price movements within one standard deviation, the brokerage margin for bitcoin futures is set at beyond two standard deviations. Some brokerage firms impose non-margin requirements such as high net account balance and open position limits in addition to regular margins. We conclude that the brokerage firms' relatively high margin and non-margin requirements impede trading activity such as short-sales and thus, liquidity and efficiency in the bitcoin futures market has been slow to develop.
Keywords: G1; 330; bitcoin; futures; Garman-Klass; volatility; liquidity; margin